2015
DOI: 10.2135/cropsci2014.07.0489
|View full text |Cite
|
Sign up to set email alerts
|

Condensed Tannins in Sainfoin: Composition, Concentration, and Effects on Nutritive and Feeding Value of Sainfoin Forage

Abstract: Legume forage is the most economical source of nutrients for ruminants. Sainfoin (Onobrychis viciifolia Scop.) is high nutritive forage growing worldwide and possesses polyphenolics including condensed tannins (CT) that contribute to some of its superior nutritional properties such as improved protein utilization, bloat‐free, and anthelmintic characteristics. This review attempts to capture the latest research in characterizing the impact of polyphenolics on the feeding value of sainfoin with an emphasis on CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 69 publications
6
76
0
5
Order By: Relevance
“…Another factor that may be involved is the content of condensed tannins in T‐SF, as these can act both directly on silage palatability and indirectly via a reduction in OM or NDF digestibility (Frutos et al ., ; Scharenberg et al ., ). However, beyond the fact that the tanniferous SF forage is recognized as highly acceptable to livestock (Khalilvandi‐Behroozyar et al ., ; Wang et al ., ), the CT content in T‐SF was moderate (1·14%) due to its dilution with the T grass, and lower than the range of concentrations associated with a decrease in feed intake (Waghorn et al ., ). Furthermore, the RC‐SF mixture that had a similar CT content was associated with one of the highest intakes.…”
Section: Discussionmentioning
confidence: 99%
“…Another factor that may be involved is the content of condensed tannins in T‐SF, as these can act both directly on silage palatability and indirectly via a reduction in OM or NDF digestibility (Frutos et al ., ; Scharenberg et al ., ). However, beyond the fact that the tanniferous SF forage is recognized as highly acceptable to livestock (Khalilvandi‐Behroozyar et al ., ; Wang et al ., ), the CT content in T‐SF was moderate (1·14%) due to its dilution with the T grass, and lower than the range of concentrations associated with a decrease in feed intake (Waghorn et al ., ). Furthermore, the RC‐SF mixture that had a similar CT content was associated with one of the highest intakes.…”
Section: Discussionmentioning
confidence: 99%
“…P. North American researchers have also explored oat and alfalfa as companion crops for irrigated birdsfoot trefoil and sainfoin (Wang et al, 2015;Hunt et al, 2016), and this involved developing a new sainfoin population for cocultivation with alfalfa. or undersowing with spring barley (Hordeum L.) as companions (Liu et al, 2008;Mora-Ortiz, 2015;.…”
Section: Cocultivation Of Legumes and Companion Cropsmentioning
confidence: 99%
“…The choice of which forage to grow will depend on the climate, soil, environment, and farming practices. The performance of these forages has been tested in pure stands and in combinations with partner species to increase the overall forage quantity and quality (Häring et al, 2008;de Koning et al, 2010;Döring et al, 2013;Lüscher et al, 2014;Wang et al, 2015).…”
Section: Agronomy Weed Control Harvesting and Processing Of Tanninmentioning
confidence: 99%
“…In contrast, Häring, Suter, Amrhein, and Lüscher () working in Switzerland found that CT concentrations in leaves doubled with age, but the leaf/stem ratio halved so that the whole plant CT concentration remained the same. Wang () attributed some of the changes in CT concentrations with time and among plant parts to optimization of CTs as defence against grazing.…”
Section: Agronomics Of Sainfoin Productionmentioning
confidence: 99%